Security analysis and portfolio management - Punithavathi pandian (Vikas publishing house pvt ltd, 2013)
Recently, even the seasoned professionals find it challenging to invest in stock markets. Students also find the topic of Security Analysis and Portfolio Management complicated. The book gives readers theoretical clarity and exhaustive coverage with an approach suitable for students. It has been written for postgraduate students studying management and commerce. It aims to throw light on this difficult subject.